2013
DOI: 10.1002/jsfa.6424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fish oil and linseed supplementation on the protein composition of milk from cows with different β‐lactoglobulin phenotypes

Abstract: The combined supplementation of fish oil and linseed had a positive impact on whey proteins in cow's milk. In addition, the phenotype of β-lactoglobulin also played a role in milk protein composition. There is therefore a clear indication that nutritional experiments should take into account not only food supplements but also the genetic variants of β-lactoglobulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…However, a different tendency of the composition of milk from the organic system was shown. In the organic system lactose had the smallest, and fat, protein and casein had the highest variation in composition 17, 32…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a different tendency of the composition of milk from the organic system was shown. In the organic system lactose had the smallest, and fat, protein and casein had the highest variation in composition 17, 32…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, β‐Lg, α‐La, serum albumin (SA), Ig, and proteose–peptone fractions have been considered the major characterized components of this fraction 32. The amount of milk protein produced by cows depends on a range of factors, including feeding level, diet type, cow health, time of year, breed, genetics, and stage of lactation 9, 10, 14, 17, 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of lactoferrin, lysozyme and phenotypic variants of β ‐lactoglobulin, e.g. β ‐LG AA , β ‐LG BB and β ‐LG AB , were established using an Agilent 1100 Series reverse phase high‐performance liquid chromatograph (Agilent Technologies, Waldbronn, Germany) according to the methodology described by Puppel et al The identification of peaks as lactoferrin, lysozyme and phenotypic variants of β ‐LG was confirmed by comparison with standards: Lf Lot 081M7021V; Lys Lot BCBD9010V; β ‐LG A Lot 100M7026V and β ‐LG B Lot 048K7003V (Sigma–Aldrich, St Louis, MO, USA). Separations were performed at ambient temperature using solvent gradient on Jupiter column C 18 300A (Phenomenex, Torrance, CA, USA).…”
Section: Experimental Designmentioning
confidence: 99%
“…The β ‐LG A variant differs from the B variant by two amino acids, aspartate‐64 and valine‐118; however, in the B variant these amino acids are substituted by glycine and alanine, respectively . Many studies were performed to investigate the effect of β ‐LG phenotypes on milk production traits, milk composition and quality . Strzałkowska et al reported that the B allele was recognised as superior for milk quality, whereas allele A is associated with yield parameters.…”
Section: Introductionmentioning
confidence: 99%